Fish mycopathology - Srivastava, R. C. (Ramesh Chandra), 1954- (New Delhi : Today & Tomorrow's Printers and Publishers ; Houston, Texas, U.S.A. : Distributed in U.S.A. by Scholarly Publications, 1987)
Studies with reference to India, chiefly on dermatomycoses.
Includes index.
Bibliography: p. [67]-103.
Keywords: Fishes -- India -- Diseases; Dermatomycoses; Fish culture -- India